Isolation And Identification Of Biosurfactant Bacteria In Anaerobic Pond Wastewater In Palm Oil Industry WWTP - Nadia Yolanda; Muhammad Hasbi; Budijono Budijono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractPalm oil waste can have a negative impact on the environment and can stimulate gene mutations in certain bacteria. The bacteria can produce bio surfactants to reduce the level of oil pollution. This study aims to identify bacteria capable of producing bio surfactants from the anaerobic pond of the palm oil industry WWTP PT. Sawit Asahan Indah, Ujung Batu, Rokan Hulu Regency. The study was conducted from April to May 2019. Samples were diluted and enriched using BHI (Brain Heart Infusion) media for 24 hours. Furthermore, samples were identified in morphological, biochemical and RNA (18SR) methods. Based on the results of the study, three types of bacteria were obtained, namely Proteus Mirabilis, Proteus vulgaris and E. coli. The Proteus Mirabilis emulsification index is 46.6%, and Proteus vulgaris is 45%. This shows that all bacteria found are able / potentially produce bio surfactants. Keywords:palm oil pollution, bio surfactant, Proteus vulgaris, Proteus mirabilis, emulsification index, RNA (18SR) method, Biodegradation.